Problem-solving teaching method and business education students’ achievement in financial accounting in public universities - Ore, Elizabeth Remilekun; David, Seyi; Alabi, Adebowale John (Journal of Management and Business Education, 2025)
This study examined the effect of the problem-solving teaching method on business education students’ academic achievement in financial accounting in public universities in Southwest Nigeria. Quasi-experimental research design was adopted with business education students. A multi-stage sampling procedure was used to select the sample size of 340 intact-class business education students from two sample universities. The instruments for the study were a self-developed achievement test tagged “Financial Accounting Achievement Test” (FAAT). A dependent sample test (paired sample t) was used to test the hypotheses. The finding in showed that the mean score of students who were taught using the problem-solving teaching method is significantly different than the mean score of students taught using the lecture method. Additionally, we revealed that the pre-test mean score is significantly different than the post-test mean score of students taught using problem-solving and lecture method.Therefore, the problem-solving teaching method enhances understanding and retention of complex financial accounting concepts.